Leadership Style and Organizational Performance in Nigerian Local Governments: Evidence from Ondo West - Dare E. Arowolo (Public Administration Quarterly, 2026)
This study examines the relationship between leadership style and organizational performance in Nigerian local governments, using Ondo West Local Government, Ondo State, as a case study. While leadership and organizational performance have been widely studied in corporate and broader national contexts, limited empirical attention has been given to Nigeria’s local government institutions. This gap constrains understanding of how participative leadership shapes employee engagement and organizational performance at the subnational level. A mixed-methods design was adopted, combining questionnaires and interviews with staff and management. Quantitative and qualitative data were analyzed using descriptive statistics and thematic analysis respectively. Findings reveal a largely non-participative leadership structure, characterized by minimal employee involvement in decision-making, particularly outside top management, with adverse effects on organizational performance. Although the single-case design limits generalizability, the study provides insights into leadership dynamics in subnational governance. It recommends institutionalizing participative leadership and inclusive decision-making frameworks to enhance organizational performance.